Professional Preparation of Teacher Educators in India- A Perspective - Yadav, Satish (Social Science Learning Education Journal, 2016)
Professionalism of any profession including education is essential for improving its quality. and maintaining standard. In education, professional teachers and teacher educators are prepared through teacher education programme. The professional teacher educators are prepared through Master of Degree in Education (M.Ed.) programme run in about 225 universities and 970 institutions in the country. Theyprepare competent and professional teachers at different stages of school education. It means the quality of school education depends upon the professional teacher educators. For making them professional, necessary knowledge, skills and attitude are inculcated among students through various activities and curriculum of M.Ed programme but this programme isÂ generally known as generic in nature and do not prepare curriculum specialists and pedagogues in areas of sciences, social sciences, languages and mathematics and at different level of school education despite many efforts made in the past.Â Therefore, there is a need to relook intoÂ this programme for preparation professional teacher educators.